The Influence Of Entrepreneurial Orientation, Product Innovation, And Digital Marketing On Marketing Performance - Syah, Fito Firman; Puspaningrum, Astrid (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Micro enterprises in the F&B sector have become an industry with crucial roles in Indonesia’s economy. One of the ways to measure the success of micro enterprises in the F&B sector is by considering their marketing performance. It is a useful concept for assessing to which extent an enterprise markets its product. The objective of this research is to identify the effects of entrepreneurial orientation, product innovation, and digital marketing on the marketing performance of micro enterprise owners in the F&B sector in Malang City. Using probability sampling and simple random sampling, 200 F&B business owners who have run their business for more than four years and applied digital marketing were selected as the respondents. The results of the multiple linear regression analysis indicate that entrepreneurial orientation, product innovation, and digital marketing have significant influences on marketing performance.